Role of human leukocyte antigen in anti-epileptic drugs-induced Stevens–Johnson Syndrome/toxic epidermal necrolysis: A meta-analysis. (November 2022) - Rashid, Muhammed; Rajan, Asha K; Chhabra, Manik; Kashyap, Ananth; Chandran, Viji Pulikkel; Venkataraman, Rajesh; Nair, Sreedharan; Thunga, Girish
Highlights: HLA polymorphism has a strong association in AED induced SJS/TEN. Asian population is more prominent to HLA polymorphism when compared to others. Carbamazepine and phenytoin induced SJS/TEN were high in those with various HLA alleles polymorphism. Abstract: Purpose: Antiepileptic drugs (AEDs) are extensively used to manage epilepsy and other comorbidities associated with seizures. Human Leukocyte Antigen (HLA) has a strong association with AED-induced severe cutaneous adverse drug reactions. Objective: We aimed to perform a systematic review and meta-analysis to identify, critically evaluate, and synthesize the best possible evidence on HLA-associated AED-induced Stevens–Johnson Syndrome/Toxic Epidermal Necrolysis (SJS/TEN). Methods: MEDLINE/PubMed, Scopus, and the Cochrane Library were searched for literature from inception up to July 2022. We included case control studies analyzing association between HLA and AED-induced SJS/TEN. We assessed the studies' risk of bias in using Quality of genetic studies (Q-genie) tool. Outcomes focused on association (risk) between HLA and AED-induced SJS/TEN. The estimated risk was presented in the form of odds ratio (OR). Results: We included 37 studies (51, 422 participants; 7027 cases and 44, 395 controls). There was a significantly higher risk of Carbamazepine-induced SJS/TEN with HLA-A (OR: 1.50; 95% CI: 1.03 to 2.17), HLA-B (OR: 1.94; 95% CI: 1.45 to 2.58), HLA-C (OR: 7.83; 95% CI: 4.72 to 12.98), and HLA-DRB1 (OR: 2.82; 95% CI: 1.94 to 4.12). Lamotrigine-induced SJS/TEN posed a higher risk with HLA-A (OR: 2.38; 95% CI: 1.26 to 4.46) and HLA-B (OR: 2.79; 95% CI: 1.75 to 4.46). Phenytoin-induced SJS/TEN showed a higher risk with HLA-A (OR: 3.47; 95% CI: 2.17 to 5.56), HLA-B (OR: 1.72; 95% CI: 1.38 to 2.15), and HLA-C (OR: 2.92; 95% CI: 1.77 to 4.83). Phenobarbital-induced SJS/TEN had a higher risk with HLA-A (OR: 6.98; 95% CI: 1.81 to 26.84), HLA-B (OR: 2.40; 95% CI: 1.39 to 4.17), and HLA-C (OR: 3.37; 95% CI: 1.03 to 11.01). Zonisamide-induced SJS/TEN was significantly associated with HLA-A*02:07 (OR: 9.77; 95% CI: 3.07 to 31.1), HLA-B*46:01 (OR: 6.73; 95% CI: 2.12 to 21.36), and HLA-DRB1×08:03 (OR: 3.78; 95% CI: 1.20 to 11.97). All other alleles of HLA were observed to have a non-significant association with AED-induced SJS/TEN. All included studies were of good quality, with a score of >50 and a mean score of 54.96 out of 77. Conclusion: Our study showed a significant association between few variants of HLA alleles and AED-induced SJS/TEN. Evidences from our study could help in population-based studies and in implementation of individualized treatment regimens. These findings could be part of translational research helping in precision therapy.